Jack and the beanstalk - Kellogg, Steven (New York : Morrow Junior Books, 1991)
A boy climbs to the top of a giant beanstalk, where he uses his quick wits to outsmart a giant and make his and his mother's fortune.
Keywords: Giants (Folklore); Fairy tales; Folklore -- England